Modelo de gestión comunicacional aplicada al posicionamiento de la empresa Solual - Fernanda Pamela, Ramos Moya (2021)
ABSTRACT: The Project aims to give solutions in the Solual Company, one that dedicated to design, built and installation of glass and aluminum in Ambato city, where it had been working during 7 years; Based on existing information the deficient of communication detected, and open the search that is low visibility in the market and it is the result of the search by the communications systems and make strategies of intern and extern aspects by studying referent models of management, design due to have relationship between them, and the Company took them to became a new model, that can apply to the Company for position.